Implementation of E-Learning Models to Improve Activities and Learning Outcomes - dianna ratnawati (Universitas Sarjanawiyata Tamansiswa, 2020)
The research aims to : (1) the application of E-learning models; (2) enhancing learning activeness; and (3) improving learning outcomes by using E-Learning models in automotive basic technology learning subjects. This research is Classroom Action Research (CAR). Data collection techniques used observation, tests and documentation. Data analysis techniques used quantitative descriptive analysis. The results showed that: (1) the application of the E-learning model was carried out by giving explanations about edmodo applications, giving examples of questions and solving them, giving students the opportunity to ask questions, opening uploaded material, giving assignments through edmodo applications, and working on them online; (2) the average percentage of learning activeness in cycle I was 57.7% with the category of moderately active, increased in cycle II to 68.9% with the active category, and increased again in the cycle III to 81.8% with very active criteria; (3) the average value in the first cycle of 65,25 with 40% mastery learning, increased to 74.25 in the second cycle with 65% mastery learning, and increased to 78.75 in the third cycle with 80% mastery learning.